1996
DOI: 10.1128/jb.178.5.1363-1373.1996
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TonB homologs in the family Enterobacteriaceae and evidence for conservation of TonB-dependent energy transduction complexes

Abstract: The transport of Fe(III)-siderophore complexes and vitamin B 12 across the outer membrane of Escherichia coli requires the TonB-dependent energy transduction system. A set of murine monoclonal antibodies (MAbs) was generated against an E. coli TrpC-TonB fusion protein to facilitate structure and function studies. In the present study, the epitopes recognized by these MAbs were mapped, and their distribution in gram-negative organisms was examined. Cross-species reactivity patterns obtained against TonB homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
108
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 53 publications
(83 reference statements)
0
108
0
Order By: Relevance
“…We have demonstrated, using the zero-length cross-linker formaldehyde, that TonB can cross-link in vivo to ExbB, to the outer membrane receptor FepA, and to at least two other proteins whose identities are currently under investigation (Skare et al, 1993). Furthermore, these cross-linking interactions are conserved amongst several other Gramnegative bacteria, suggesting that they represent meaningful interactions (Larsen et al, 1996). It has been clearly demonstrated that TonB-dependent energy transduction requires, either directly or indirectly, the cytoplasmic membrane pmf (Bradbeer, 1993).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We have demonstrated, using the zero-length cross-linker formaldehyde, that TonB can cross-link in vivo to ExbB, to the outer membrane receptor FepA, and to at least two other proteins whose identities are currently under investigation (Skare et al, 1993). Furthermore, these cross-linking interactions are conserved amongst several other Gramnegative bacteria, suggesting that they represent meaningful interactions (Larsen et al, 1996). It has been clearly demonstrated that TonB-dependent energy transduction requires, either directly or indirectly, the cytoplasmic membrane pmf (Bradbeer, 1993).…”
Section: Discussionmentioning
confidence: 98%
“…In Escherichia coli, and presumably other Gram-negative bacteria (Larsen et al, 1996), TonB protein couples the cytoplasmic membrane pmf to active transport of ironsiderophore complexes and vitamin B12 across the outer membrane and into the periplasmic space. In doing so, it requires two cytoplasmic membrane proteins, ExbB and ExbD, as well as the outer membrane receptors through which those nutrients are transported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, specific surface receptors promote the translocation of these various substrates by an energized mechanism. This energy-dependent transport is mediated by a cytoplasmic membrane complex consisting of three proteins: TonB, ExbB and ExbD (Postle 1993;Larsen et al 1996). Current models consider TonB to function as the energy transducer that couples the proton motive force of the cytoplasmic membrane to drive ligand translocation through the outer membrane receptors.…”
Section: Biological Contextmentioning
confidence: 99%
“…In addition, complexes between TonB or its homologues and other proteins (ExbB, ExbD, and as yet unidentified proteins) were detected with anti-E. coli TonB monoclonal antibodies (mAbs 1 ; Ref. 16). These findings demonstrate that the TonB-dependent energy transduction system is shared among many Gram-negative bacteria and suggest that high affinity energy-dependent iron uptake in Gram-negative aerobes is accomplished using TonB and its accessory proteins (16).…”
mentioning
confidence: 99%